Lenvatinib versus sorafenib as second-line therapy following progression on atezolizumab–bevacizumab in patients with unresectable hepatocellular carcinoma: a multicenter retrospective study from Korea and Japan - Jaekyung Cheon; Shigeo Shimose; Hyung-Don Kim; Takashi Niizeki; Min-Hee Ryu; Tomotake Shirono; Baek-Yeol Ryoo; Hideki Iwamoto; Changhoon Yoo (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose Atezolizumab–bevacizumab (AB) is the established first-line systemic therapy for patients with unresectable hepatocellular carcinoma (uHCC). However, the optimal second-line treatment for patients unresponsive to AB remains undefined. Patients and methods This multicenter, retrospective study included patients with uHCC who underwent second-line treatment with lenvatinib (LEN) or sorafenib (SOR) after AB failure at two academic centers between June 2018 and November 2023. Treatment response was assessed using Response Evaluation Criteria in Solid Tumors (RECIST) v1.1 and modified RECIST. Propensity score matching (PSM) was employed to mitigate confounding bias. Results A total of 123 were included in the final analysis, 56 patients received LEN, and 67 received SOR. Before PSM, LEN was associated with significantly improved progression-free survival (PFS) compared with SOR (median 4.9 vs. 3.3 months, p < 0.001); however, no significant difference in overall survival (OS) was observed (median 13.2 vs. 11.5 months, p = 0.651). After PSM, in a cohort of 50 patients (25 per each group), LEN maintained its PFS advantage over SOR (median 4.8 vs. 3.3 months, p = 0.046), while the median OS was longer with LEN but not statistically different (median 11.4 vs. 7.9 months, p = 0.197). Response rates were 40% for LEN and 12% for SOR (p = 0.021) based on modified RECIST, and 12% and 8% (p = 0.728) based on RECIST v1.1, respectively. Conclusion In this real-world study, LEN demonstrated superior PFS and comparable OS to SOR as second-line treatment for uHCC after progression on AB.